Family structure and women’s mental well-being: how family stressors explain mental health inequalities between lone and partnered mothers - McDonnell, Cadhla; Gracia, Pablo (Frontiers in Sociology, 2024)
Lone mothers have been found to report lower average mental health than partnered mothers. Following the ‘stress process model’, disparities in women’s mental health by family structure could be explained by lone mothers’ higher exposure to multiple forms of stressors, compared to partnered mothers. Yet, this hypothesis has not been tested in previous studies. This study analysed four waves of longitudinal data from the Growing Up in Ireland study, spanning between the year when women gave birth (2008) to 9 years later (2017) (N = 5,654 women), to examine how family stressors (i.e., financial strain, caregiving strain, work-related strain, and parental conflict) influence mothers’ depressive symptoms by family structure. Analyses applied random-effects models and Karlson-Holm-Breen (KHB) decomposition techniques, combined with different model specifications as robustness checks (i.e., fixed-effects). Results indicate that: (1) net of sociodemographic factors, lone mothers experience higher levels of depressive symptoms than partnered mothers, with additional analyses confirming that transitioning from partnered to lone mother is associated with higher depressive symptoms, and from lone to partnered mother with reduced depressive symptoms; (2) although 41% of the observed statistical association between family structure and mothers’ depressive symptoms is direct, a larger 59% of this mental health gap is mediated by inequalities between lone and partnered mothers in their exposure to family stressors; and (3) the largest share of the observed mediation by family stressors is explained by lone mothers’ higher risks of current and past caregiving strain and parental conflict, but also by their current higher financial strain. Overall, this study suggests that lone mothers’ lower mental health, compared to partnered mothers, is largely explained by disparities in exposure to family stressors, pointing to how accumulated caregiving and parental stressors, as well as poverty risks, are key explanatory factors behind the mental well-being disadvantage that lone mothers face.